Removal of metals and emergent contaminants from liquid digestates in constructed wetlands for agricultural reuse - Porras-Socias, Pau; Tomasino, Maria Paola; Fernandes, Joana P.; De Menezes, Alexandre B.; Fernández, Belén; Collins, Gavin; Alves, Maria João; Castro, Ricardo; Gomes, Carlos R.; Almeida, C. Marisa R.; Mucha, Ana Paula (Frontiers in Microbiology, 2024)
Given the increasing pressure on water bodies, it is imperative to explore sustainable methodologies for wastewater treatment and reuse. The simultaneous presence of multiples contaminants in complex wastewater, such as the liquid effluents from biogas plants, can compromise biological treatment effectiveness for reclaiming water. Vertical subsurface flow constructed wetlands were established as low-cost decentralised wastewater treatment technologies to treat the liquid fraction of digestate from municipal organic waste with metals, antibiotics, and antibiotic resistance genes, to allow its reuse in irrigation. Twelve lab-scale planted constructed wetlands were assembled with gravel, light expanded clay aggregate and sand, testing four different treating conditions (liquid digestate spiked with oxytetracycline, sulfadiazine, or ofloxacin, at 100 µg/ L, or without dosing) during three months. Physicochemical parameters (pH, chemical oxygen demand (COD), nutrients, metals, and antibiotics), the microbial communities dynamics (through 16S high-throughput sequencing) and antibiotic resistance genes removal (qPCR) were monitored in influents and effluents. Systems removed 85.8 -96.9 % of organic matter (as COD), over 98.1 % of ammonium and phosphate ions, and 69.3 -99.4 % of nitrate and nitrite ions, with no significant differences between the presence or absence of antibiotics. Removal of Fe, Mn, Zn, Cu, Pb and Cr exceeded 82 % in all treatment cycles. The treatment also removed oxytetracycline, sulfadiazine and ofloxacin over 99 %, and decreased intl1, tetA, tetW, sul1 and qnrS gene copies. Nonetheless, after 3 months of ofloxacin dosing, qnrS gene started being detected. Removal processes relied on high HRT (14 days) and various mechanisms including sorption, biodegradation, and precipitation. Microbial community diversity in liquid digestate changed significantly after treatment in constructed wetlands with a decrease in the initial Firmicutes dominance, but with no clear effect of antibiotics on the microbial community structure. Removals above 85 % and 94 % were observed for Streptococcus and Clostridium, respectively. Results suggest that vertical subsurface flow constructed wetlands were a suitable technology for treating the liquid digestate to reuse it in irrigation agricultural systems, contributing to the circular bioeconomy concept. However, a more profound understanding of effective wastewater treatment strategies is needed to avoid antibiotic resistance genes dissemination.